(untitled) (European Journal of Pure and Applied Mathematics, 2010)
The concept of an S âˆ’ Linear ADL is defined and characterized in terms of the S âˆ’ prime ideals and S âˆ’ prime filters.Â Equivalent condition for an ADL R to become a (dually)B âˆ’ relatively normal ADL in terms of minimal prime ideals(filters) and B âˆ’ maximal ideals(filters) is obtained, where B is the Birkhoff centre of R.